Dari Naskah Kuno Menjadi Komik: Alih Wahana Teks Mahabharata ke dalam Komik Wayang Ala Manga - Widyaningrum, Rahmatia Ayu (Sekolah Pascasarjana Institut Kesenian Jakarta, 2023)
This article describes the media transfer process of the long epic Mahabharata into a comic series entitled Baratayuda. The transfer media for the Mahabharata text analyzed in this study is the end of chapter (parwa) four, “Virata Kingdom”, and the beginning of chapter (parwa) five of the Mahabharata epic, namely “Preparations for War”. This part was transferred in the form of the Baratayuda comic series volume 4 entitled “Midnight Negotiations”. The characters in the Baratayuda comic are compared with the manga comic, Saint Seiya. The Baratayuda comic does not directly imitate the character of the knight in Saint Seiya. However, when reading the Barayuda comic, the reader’s association will immediately focus on the manga comic because the characters highlighted are very similar to the manga knight comic characters because of the similarity in the visualization of the five hero characters in both comics. as well as panels - the Baratayuda comic which adapts the manga comic model, Saint Seiya. The transfer of the Mahabharata text is a form of creativity in processing the manuscript text into a more popular form. Therefore, this research provides an illustration that ancient manuscripts that are difficult to reach by the general public can be transformed into a more contemporary form so that they can be accessed by the wider community. Tulisan ini menguraikan proses alih wahana epos panjang Mahabharata menjadi serial komik yang berjudul Baratayuda. Alih wahana teks Mahabharata yang dianalisis dalam kajian ini adalah akhir parwa empat, ”Kerajaan Wirata”, dan awal parwa lima epos Mahabharata, yaitu ”Persiapan Perang”. Bagian tersebut dialihwahanakan dalam bentuk komik seri Baratayuda jilid 4 yang berjudul ”Perundingan Tengah Malam”. Karakter tokoh dalam komik Baratayuda dibandingankan dengan komik manga, Saint Seiya. Komik Baratayuda pada dasarnya tidak serta merta meniru secara langsung karakter tokoh ksatria dalam Saint Seiya. Namun, ketika membaca komik Baratayuda, asosiasi pembaca akan langsung tertuju pada komik manga karena karakter yang ditonjolkan sangat mirip dengan karakter komik ksatria manga sebab kesamaan visualisasi lima tokoh hero pada keduanya. Pembahasan dalam tulisan ini juga menguraikan kecenderungan bentuk karakater—baik tokoh, background, maupun panel—komik Baratayuda yang mengadaptasi model komik manga, Saint Seiya. Alih wahana teks Mahabharata merupakan bentuk kreativitas dalam mengolah teks manuskrip menjadi bentuk yang lebih populer. Oleh sebab itu, penelitian ini memberikan gambaran bahwa naskah kuno yang sulit dijangkau oleh masyarakat umum dapat diubah menjadi bentuk yang lebih kontemporer agar dapat diakses oleh masyarakat luas. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack// This page is in Indonesian Translate to English AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Indonesian to EnglishPRO Never translate Indonesian Never translate jurbalurban.pascasarjanaikj.ac.id